2018
DOI: 10.1111/jcmm.13794
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cell network volume is reduced in the terminal bowel of ageing mice

Abstract: Ageing is associated with impaired neuromuscular function of the terminal gastrointestinal (GI) tract, which can result in chronic constipation, faecal impaction and incontinence. Interstitial cells of cajal (ICC) play an important role in regulation of intestinal smooth muscle contraction. However, changes in ICC volume with age in the terminal GI tract (the anal canal including the anal sphincter region and rectum) have not been studied. Here, the distribution, morphology and network volume of ICC in the ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Interestingly, loss of ICC was first observed in the stomach, followed by the intestine and colon, indicating that gastric ICC functionality may be the first affected during ageing. Additionally, similar changes in ICC network volumes have been found in the terminal bowel of ageing mice [ 82 ]. Whilst thorough molecular information regarding ICC and ageing is yet to be elucidated, these data indicate that a change in ICC functionality may, in part, affect GI motility with age.…”
Section: Icc and Gi Disorderssupporting
confidence: 62%
“…Interestingly, loss of ICC was first observed in the stomach, followed by the intestine and colon, indicating that gastric ICC functionality may be the first affected during ageing. Additionally, similar changes in ICC network volumes have been found in the terminal bowel of ageing mice [ 82 ]. Whilst thorough molecular information regarding ICC and ageing is yet to be elucidated, these data indicate that a change in ICC functionality may, in part, affect GI motility with age.…”
Section: Icc and Gi Disorderssupporting
confidence: 62%
“…Another study showed that Cajal bodies (ICC), which have an abnormal number of mesenchymal cells, can cause changes in the cell morphology and network structure, which can slow down colonic peristalsis and induce constipation, which may be the basic pathogenesis of slow transit constipation. 48,49 c-Kit is one of the specic markers of ICC, and is a factor in maintaining ICC proliferation and growth under normal conditions, 50 SCF is a natural ligand of the c-Kit receptor. 51 Studies have found that the concentration of SCF is very important to the cultivation of the ICC.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal number of mesenchymal cells and changes in cell morphology and network structure can slow down colonic peristalsis and induce constipation. c-Kit is a specific marker of interstitial cells of Cajal (ICC) (Kim et al, 2019) and a factor in maintaining ICC proliferation and growth under normal conditions (Gamage et al, 2018;Jiang et al, 2015). C-kit protein is expressed in many cells in the body, including ICC and mast cells in the intestine.…”
Section: Mechanism Of Lactic Acid Bacteria Isolated From Xinjiang Yog...mentioning
confidence: 99%